Approaches to the kangaroo method in the humanization of newborns: A systemic review (International Seven Journal of Health Research, 2023)
Introduction: Due to technological advances in Neonatal Units not being sufficient to provide humanized care and not meeting the needs of newborns, the Kangaroo Method was created by the Ministry of Health with the aim of providing newborns with quality care. Objective: To describe the approaches of the Kangaroo Method in the humanization of the newborn, through a qualitative systemic review. Methods: Using the terms "kangaroo method", "humanized care" and "newborns", publications were selected from the PUBMED, LILACS and SCIELO databases, as well as dissertations and manuals from 2017 to 2023. Results: 45 materials were found, of which 25 were excluded after applying the criteria defined for the textual production of this article, 5 because they were not related to the topic, leaving 6 articles selected to read the abstracts, leaving 9 studies. Final considerations: The Kangaroo Method has stages that aim to promote humanized care for the NB by establishing a bond between the NB and the mother through contact with the mother's or father's body, as well as providing humanized care for health professionals in terms of reducing morbidity and mortality in premature neonates.